Evaluation of the influence of salinity on germination, development and diversity of endophytic microorganisms of the leguminous Mucuna aterrima (Research, Society and Development, 2018)
The use of legumes is a method for the recovery of soil fertility, since in addition to providing organic matter also fixes nitrogen to the soil. Therefore, relevant research on the legume capacity for use in saline soils has been shown to assist the recovery of these legumes. Thus, the objective of this work was to evaluate the influence of salinity on germination, development and isolation of endophytic microorganisms of the black mucuna legume (Mucuna aterrima). The experiment was carried out in a completely randomized design (5x3) with five treatments (0.0, 0.025, 0.05, 0.1, 0.2 mol NaCl/L) and three replications. The percentage of germination, the dry mass of the root, stem and leaves were analyzed and counted bacteria and endophytic fungi. As a result, there was a reduction in the percentage of the germination rate with the increase in salinity. Although no interference was observed in the richness of microorganisms, bacterial resistance to salinity was verified. Thus, this study indicates that black mucuna is not indicated for planting in soils with saline concentrations higher than 0.1 mol NaCl/L, because this concentration presents toxicity to the plant and does not favor its germination.